Infliximab and risk of serious infection in patients with psoriasis. (4th February 2019) - Yiu, Z.Z.N.; Ashcroft, D.M.; Evans, I.; McElhone, K.; Lunt, M.; Smith, C.H.; Walton, S.; Murphy, R.; Reynolds, N.J.; Ormerod, A.D.; Griffiths, C.E.M.; Warren, R.B.; et al.
Summary: This study from the UK used information from a data source known as the British Association of Dermatologists Biologic Interventions Register, or BADBIR, which was established to collect information on the use and outcomes of new biologic treatments, versus nonbiologic systemic treatments, for skin disease. In this study, information on the use of the biologic treatment, Infliximab, used in a number of skin diseases including psoriasis was compared with other systemic therapies (systemic means treatments that work on the whole body, as opposed to something applied just to the skin). The focus of this work was on the occurrence of serious infections in patients under different treatments. These serious infections were those where patients had prolonged admissions to hospital, were treated with intravenous antibiotics or where they died. The investigation also considered the possible effects of other conditions which might also have led to the development of serious infections in both groups. The main conclusion of this work was that the likelihood (risk) of serious infection in patients receiving Infliximab compared with those receiving other systemic therapies was doubled. The main infections were either those affecting the lungs or skin and soft tissue infections. These infections were mainly seen in the first six months after patients started on Infliximab. This is an important finding as counselling patients on this risk will form a key part of preparatory assessment prior to use of this medicine. The authors point out that similar information is not yet available for other biologics used for the treatment of skin disease and these may also be associated with an increased risk of infection, although screening for existing chronic infections, such as tuberculosis, forms an important part of the pre‐treatment investigation of potential candidates for these biologic medications. Abstract : Linked Article:  Yiu et al. Br J Dermatol 2019;180 :329–337